2015
DOI: 10.1109/tgrs.2015.2444351
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Pol-InSAR Measurements to Vegetation Parameters

Abstract: Estimation of forest height from combined polarimetric and interferometric synthetic aperture radar (Pol-InSAR) measurements has been the focus of radar remote sensing studies in the past decade. The simplicity of the random-volume-overground (RVoG) model makes it one of the most widely used candidates for estimating canopy height. However, the polarization-independent extinction coefficient assumption in the RVoG model fails in some certain types of the canopies, as suggested by the oriented-volume-over-groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Numerous tests showed that all solutions fulfilling the condition of 5% of the RVoG line length provide the accuracy required to ensure satisfactory parameter estimations. When the resulting optimized solution does not converge to the established criterion, a different initial guess for the vegetation height (which in turn is known to be the most sensitive parameter [18], [19], [24], [28]) is generated randomly using a uniform distribution. The ranges in which the new guess is generated are the same as those we use to generate the simulated scenes (later specified in Section IV and Table II): h v,random ∈ [0, HoA /2] m for the crops and h v,random ∈ [2, HoA /2] m for the forests.…”
Section: B Parameter Retrieval In Bistatic Configurations With Dominmentioning
confidence: 99%
“…Numerous tests showed that all solutions fulfilling the condition of 5% of the RVoG line length provide the accuracy required to ensure satisfactory parameter estimations. When the resulting optimized solution does not converge to the established criterion, a different initial guess for the vegetation height (which in turn is known to be the most sensitive parameter [18], [19], [24], [28]) is generated randomly using a uniform distribution. The ranges in which the new guess is generated are the same as those we use to generate the simulated scenes (later specified in Section IV and Table II): h v,random ∈ [0, HoA /2] m for the crops and h v,random ∈ [2, HoA /2] m for the forests.…”
Section: B Parameter Retrieval In Bistatic Configurations With Dominmentioning
confidence: 99%
“…In addition to the height of the vegetation, extinction coefficient and other vertical parameters can be derived. Based on the PolInSAR complex coherent coefficient model proposed by Oveisgharan [9], Papathanassiou transforms the inversion procedure into a classical non-liner parameter estimation problem, which is referred to as the six-dimension non-liner iteration method. It provides many valuable parameters simultaneously, however, calculation is time consuming, and it strongly depends on the initial value and tends to fall into the local optimal solution [10].…”
Section: Introductionmentioning
confidence: 99%